1999
DOI: 10.1002/(sici)1097-4628(19990919)73:12<2391::aid-app9>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Microwave irradiation of nadic-end-capped polyimide resin (RP-46) and glass-graphite-RP-46 composites: cure and process studies

Abstract: ABSTRACT:Microwave energy was investigated to cure nadic-end-capped polyimide precursors (RP-46 resin) using a Cober Electronics Model LBM 1.2A/7703 microwave oven at a frequency of 2.45 GHz. Both neat resin samples and glass cloth and hybrid glass cloth-graphite cloth-RP-46 resin composites were studied. For the resin studies, the effect of various parameters, such as power level, sample size, processing temperature, time, and graphite fiber absorber, were investigated. The variables investigated with the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…The mechanical properties were also much better. It can be argued that the ceramic plates absorbed a large amount of microwaves and converted into heat which was then conducted to the last 4 specimens [22].…”
Section: Casementioning
confidence: 55%
See 4 more Smart Citations
“…The mechanical properties were also much better. It can be argued that the ceramic plates absorbed a large amount of microwaves and converted into heat which was then conducted to the last 4 specimens [22].…”
Section: Casementioning
confidence: 55%
“…The HAZ (heat affected zone) seemed to be confined to the lapped area, which could be bent by hand easily and outside which the warming and heating effect of microwave energy could not be felt. The tensile tests revealed that sixty percent of the failures were due to the adhesive and took place at the joints [11,[20][21][22].…”
Section: Casementioning
confidence: 99%
See 3 more Smart Citations